A Reliable and Secure AODV Protocol for MANETs - Kumar Singh Yadav, Ajit; K. Yadav, Rajesh (International Journal of Engineering and Technology, 2018)
In recent years, Mobile ad hoc networks ((MANETs) have generated great interest among researchers in their implementation under several computing environments. However, MANETs are highly susceptible to various security attacks due to their inherent characteristics. The ad hoc on demand distance vector (AODV) is most suitable routing protocol for mobile adhoc networks in which resource consumption attacks are frequent if it is not detected timely. In this paper, we have proposed a scheme to detect as well as overcome black hole attacks using an Intrusion Detection System (IDS). The proposed scheme is implemented using network simulator 2(NS2) to compare its performance against the standard AODV with and without attack. The results of the simulation show that proposed scheme optimizes the end-to-end delay, normalized routing load, packet delivery fraction and average throughput in comparison with AODV protocols under black hole attack.Â Â